Beta-blockers in older patients with heart failure and preserved ejection fraction: class, dosage, and outcomes - Patel, Kanan (2014)
BACKGROUND: We examined the clinical effectiveness of beta-blockers considered evidenced-based to heart failure and reduced ejection fraction (HFrEF) and recommended target dosing in older adults with HF and preserved ejection fraction (HFpEF). METHODS: In OPTIMIZE-HF (2003–2004) linked to Medicare (2003–2008), of the 10,570 older (age ≥65, mean, 81 years) adults with HFpEF (EF ≥40%, mean 55%), 8373 had no contraindications to beta-blocker therapy. After excluding 4614 patients receiving pre-admission beta-blockers, the remaining 3759 patients were potentially eligible for new discharge prescriptions for beta-blockers and 1454 received them. We assembled a propensity-matched cohort of 1099 pairs of patients receiving beta-blockers and no beta-blockers, balanced on 115 baseline characteristics. Evidence-based beta-blockers for HFrEF, namely, carvedilol, metoprolol succinate, and bisoprolol and their respective guideline-recommended target doses were 50, 200, and 10 mg/day. RESULTS: During 6 years of follow-up, new discharge prescriptions for beta-blockers had no association with the primary composite endpoint of all-cause mortality or HF rehospitalization (hazard ratio, 1.03; 95% confidence interval CI, 0.94–1.13; p=0.569). This association did not vary by beta-blocker evidence class or daily dose. Hazard ratios for all-cause mortality and HF rehospitalization were 0.99 (95% CI, 0.90–1.10; p=0.897) and 1.17 (95% CI, 1.03–1.34; p=0.014). The latter association lost significance when higher EF cutoffs of ≥45%, ≥50% and ≥55% were used. CONCLUSIONS: Initiation of therapy with beta-blockers considered evidence-based for HFrEF and in target doses recommended for HFrEF had no association with the composite or individual endpoints of all-cause mortality or HF rehospitalization in HFpEF.